Boys' responses to the integration of advertising and entertaining content. Issue 3 (17th August 2015) - van Reijmersdal, Eva A.; Rozendaal, Esther; Buijzen, Moniek
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purposes of this paper are to investigate the effects of integrated advertising formats on the persuasion of children, children's awareness of the persuasive intent of these formats and how this awareness mediates the level of persuasion. Design/methodology/approach – An one-factor between-subjects experiment was conducted among 117 boys from 8 to 12 years old. Findings – This study showed that boys were more aware of the persuasive intent of a non-integrated catalog than of a brand-integrated magazine. In addition, higher awareness of the persuasive intent of the catalog enhanced persuasion in boys. Research limitations/implications – This study only focused on boys' responses and not on girls. Practical implications – Findings imply that advertisers could focus on non-integrated print advertising formats, such as catalogs, to promote positive product attitudes among boys. Catalogs are also a more ethical way of communicating to boys because boys are generally aware of catalogs' persuasive intent. Social implications – This study implies that even if children have sufficient persuasion knowledge, they do not necessarily use it to critically evaluate advertising. Originality/value – This paper is the first to systematically test the differences in effects of brand-integrated magazines versus catalogs targeted toward children. Importantly, it shows that persuasion knowledge plays a fundamentally different role in the persuasion process of children than of adults: awareness of the persuasive intent of catalogs increases persuasion among boys, whereas previous studies among adults showed opposite results.